Evaluating the Effectiveness of Accelerated and Accelerated Cornea Pulsing Crosslinking Based on the Presence of a Demarcation Line - L. I. Khalimova (Oftalʹmologiâ)
Purpose of the study is to assess the state of the demarcation line of the stroma after accelerated and pulsed accelerated ultraviolet cornea crosslinking. Patients and methods. Clinical observations included 24 patients (31 eyes) with keratoconus (KC), aged 18–46 years, men — 11 (45.9 %), women — 13 (54.1 %). Accelerated (a-CXL) crosslinking was carried out in continuous mode with a power of 18 mW/cm2 for 5 minutes (13 eyes), pulsed accelerated (i-ACXL) with a power of 18 mW/cm2 for 10 minutes, in mode 1 sec light / 1 sec pause (18 eyes). Conducted generally accepted and additional methods of ophthalmic research. The follow-up periods were 1, 3, and 6 months after surgery. Results. According to optical coherent tomography, the demarcation line was detected in all cases after a-CXL and i-ACXL. At 1 month after the crosslinking, there were no significant differences between the a-CXL and i-ACXL groups in terms of uncorrected visual acuity, corrected visual acuity, maximal correction. The average depth with demarcation at 1 month after the procedure in the central zone of the cornea was 216.41 ± 36.67 μm in the a-CXL group and 236.41 ± 37.08 μm in the i-ACXL group. Using confocal microscopy in vivo in both groups 1 month after surgery apoptosis of keratocytes and stromal edema were detected. A gradual restoration of the cornea to its original state was observed after 6 months. Conclusion. Research results have shown that accelerated and pulsed accelerated cross-linking are safe and effective technologies to stabilize the progression of keratoconus. Both crosslinking protocols provide a significant reduction in the duration of the procedure compared to the traditional one. Revealed deeper arrangement of the demarcation line when performing pulsed accelerated crosslinking compared to the accelerated. Further long-term and more extensive studies of accelerated and pulsed accelerated cornea ultraviolet crosslinking will provide improved information on their effectiveness in the long-term.